Integrating Digital Literacy in Christian Religious Education: a Study of Student in Politeknik Negeri Ambon - Pariama, Leonardo Stevy (PT. BATARI EDU CALYA, 2024)
This study investigates the integration of digital literacy into Christian Religious Education (CRE) at Politeknik Negeri Ambon, examining its impact on student engagement, academic performance, and ethical development. Employing a mixed-methods approach, the research involved surveys, assessments, interviews, and focus groups with students and educators. The results indicated that higher levels of digital literacy significantly enhance student engagement and academic performance in CRE, while also positively influencing moral and ethical development. However, challenges such as inadequate infrastructure, lack of training, and resistance to change were identified as barriers to successful integration. The study concludes that with appropriate support and resources, integrating digital literacy into CRE can provide a comprehensive educational experience that aligns with both technological advancements and religious principles.